2019
DOI: 10.1186/s12014-019-9242-4
|View full text |Cite
|
Sign up to set email alerts
|

Plasma proteomic and autoantibody profiles reveal the proteomic characteristics involved in longevity families in Bama, China

Abstract: Background Chinese Bama Yao Autonomous County is a well-known longevity region in the world. In the past 30 years, population and genome studies were undertaken to investigate the secret of longevity and showed that longevity is the result of a combination of multiple factors, such as genetic, environmental and other causes. In this study, characteristics of the blood plasma proteomic and autoantibody profiles of people from Bama longevity family were investigated. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…Inclusion criteria for a manuscript included healthy individuals, proteomics results published on or after 2010, publications/authors provided list of significant/all proteins. Thirty three manuscripts met the inclusion criteria, including 12 that covered human plasma (Enroth et al, 2015; Lehallier et al, 2019; Lind et al, 2019; Menni et al, 2015; Ngo et al, 2016; Orwoll et al, 2018; Santos‐Lozano et al, 2020; Sun et al, 2018; Tanaka et al, 2018; Wang, Zhu, et al, 2019; Wang, Zhang, et al, 2019; Ye et al, 2019), 9 from 14 different matrices in humans (Baird et al, 2012; Bakun et al, 2014; Bell‐Temin et al, 2019; Gueugneau et al, 2014; Heinze et al, 2018; Hennrich et al, 2018; Ubaida‐Mohien et al, 2019; Waldera‐Lupa et al, 2014; Wang, Wang, et al, 2018), and 12 publications covering 21 different species/matrices (Amin et al, 2020; Angelidis et al, 2019; Braun et al, 2016; Cutler et al, 2017; Drulis‐Fajdasz et al, 2018; Gebert et al, 2020; Heinze et al, 2018; Kelley et al, 2018; Meng et al, 2020; Stauch et al, 2015; Wang, Zhu, et al, 2019; Yu et al, 2020). The age range of participants included in these studies spanned from 14 to 103 years, and measures were carried out using multiple platforms including but not limited to liquid chromatography–mass spectrometry (LC‐MS)‐based proteomics, multiplexed proteomic assay using modified aptamers (SOMAscan) and Proximity Extension Assay (PEA, O‐Link) (Gold et al, 2010; Lundberg et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Inclusion criteria for a manuscript included healthy individuals, proteomics results published on or after 2010, publications/authors provided list of significant/all proteins. Thirty three manuscripts met the inclusion criteria, including 12 that covered human plasma (Enroth et al, 2015; Lehallier et al, 2019; Lind et al, 2019; Menni et al, 2015; Ngo et al, 2016; Orwoll et al, 2018; Santos‐Lozano et al, 2020; Sun et al, 2018; Tanaka et al, 2018; Wang, Zhu, et al, 2019; Wang, Zhang, et al, 2019; Ye et al, 2019), 9 from 14 different matrices in humans (Baird et al, 2012; Bakun et al, 2014; Bell‐Temin et al, 2019; Gueugneau et al, 2014; Heinze et al, 2018; Hennrich et al, 2018; Ubaida‐Mohien et al, 2019; Waldera‐Lupa et al, 2014; Wang, Wang, et al, 2018), and 12 publications covering 21 different species/matrices (Amin et al, 2020; Angelidis et al, 2019; Braun et al, 2016; Cutler et al, 2017; Drulis‐Fajdasz et al, 2018; Gebert et al, 2020; Heinze et al, 2018; Kelley et al, 2018; Meng et al, 2020; Stauch et al, 2015; Wang, Zhu, et al, 2019; Yu et al, 2020). The age range of participants included in these studies spanned from 14 to 103 years, and measures were carried out using multiple platforms including but not limited to liquid chromatography–mass spectrometry (LC‐MS)‐based proteomics, multiplexed proteomic assay using modified aptamers (SOMAscan) and Proximity Extension Assay (PEA, O‐Link) (Gold et al, 2010; Lundberg et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…164,187 Specifically, the plasma proteomic and autoantibody profiles of offspring of long-lived families and age-related controls were compared. 187 TMT labeling enabled the quantification of over 500 proteins, out of which 12 proteins were differentially expressed between the two groups (proteins with increased levels: LPA, DEFA3, immunoglobulin, BLVRB, and PDIA3; proteins with reduced levels: TPM, GBA, DSG2, SRC, CHGA, ITGB3, and TAGLN2). In a second study, 175 proteins were identified to be differentially abundant between the groups, and a panel of five proteins (MMP2, CCL5, PF4, IGFBP2, and C9) may serve as biomarkers to predict healthy aging and longevity.…”
Section: ■ Agingmentioning
confidence: 99%
“…The Bama Yao Autonomous County in China is one of the well-known longevity regions. Multiple genome and population studies have been carried out in the past, and recently, proteomics studies have been pursued. , Specifically, the plasma proteomic and autoantibody profiles of offspring of long-lived families and age-related controls were compared . TMT labeling enabled the quantification of over 500 proteins, out of which 12 proteins were differentially expressed between the two groups (proteins with increased levels: LPA, DEFA3, immunoglobulin, BLVRB, and PDIA3; proteins with reduced levels: TPM, GBA, DSG2, SRC, CHGA, ITGB3, and TAGLN2).…”
Section: Agingmentioning
confidence: 99%
“…In our previous studies [ 6 , 10 ], we found some differentially expressed proteins (DEPs) between Bama longevous family group and normal controls from non-longevous region of China. Some of these DEPs such as PGK1, ENO1, LDHA, LDHB, PKM, and GAPDH, were glycolysis/gluconeogenesis-related proteins.…”
Section: Introductionmentioning
confidence: 99%